Implementing CYP2C19-guided clopidogrel therapy: a scoping review of pharmacogenomic testing services - Patel, Tark J.; Wehbe, Eman; Hughes, Stephen; Patanwala, Asad E.; Kritharides, Leonard; Lal, Sean; Patel, Sanjay; Stocker, Sophie L. (The pharmacogenomics journal, 2025)
Pharmacogenomic testing for CYP2C19 helps personalise clopidogrel therapy and reduces the risk of experiencing a secondary myocardial infarction in individuals with impaired CYP2C19 function. Routine testing, however, is uncommon and it is proposed that the key requirements and processes of testing services are poorly understood. This scoping review aimed to explore the literature for CYP2C19 testing services for clopidogrel and identify their commonalities to inform the design and delivery of future services. In total, 37 eligible studies describing services across hospital and community settings were retrieved. Key elements of delivery included a multi-disciplinary approach involving physicians and pharmacists, provision of pre-implementation training and education, and electronic communication of test results. Result integration into clinical decision support systems improved the practical application of pharmacogenomic testing. The identification of the key requirements and processes may be used by institutions looking to design and deliver CYP2C19 testing services to guide clopidogrel therapy.